The multi-airline p-hub median problem applied to the African aviation market - Adler, Nicole; Njoya, Eric Tchouamou; Volta, Nicola (Elsevier, 2017)
Despite growth in research on air transport in Africa in recent years, little is known about the adequacy of the infrastructure to sustain potential future air traffic expansion. The continent has experienced growth in domestic, intra- and inter-continental air traffic services over the past two decades that we project will continue over the medium term. Applying a gravity model in which corruption, conflict, common language and land-locked indices contribute to the demand estimation, we forecast annual intra-African growth of 8.1% up to 2030. As witnessed in established markets, deregulation will likely result in hub-spoke network designs in order to accommodate demand efficiently if mobility and access is to be encouraged. In this research, we modify the p-hub median problem in order to identify multiple, economically viable, hub-spoke networks that would adequately serve the intra- and inter-continental demand for air transport. Aside from current hubs, namely Cairo (Egypt), Addis Ababa (Ethiopia) and Johannesburg (South Africa), future hubs could include airports in the North that serve European-African flows, such as Algiers, and Nigeria in the West due to its relatively large population and wealth. By 2030, we also find that demand is sufficient to justify an additional hub in central Sub-Saharan Africa, such as Lusaka (Zambia). However, this would be dependent on the implementation of liberalisation policies as set out in the Yamoussoukro Decision.
Keywords: African aviation market; P-hub median; Demand forecasting; Capacity analysis